Alternative prize rank distributions for higher gender equity in sports - Martens, M.; Starflinger, V. (Journal of Sports Analytics, 2025)
In many sports, women receive less prize money than men, frequently by having fewer prize ranks. This issue has been discussed extensively over decades. While many people consider different prize structures for men and women unfair, others argue, e.g., that men attract greater public interest or that the competition is harder among men—particularly, when more men than women participate or when the competition duration is longer for men. In this paper, we focus on the discussion of fairness in the distribution of prize ranks in endurance sports, concerning the number of prize ranks for men versus that for women, compared to the severity of the competition. We present two methods to distribute prize ranks across gender based on the individual performances w.r.t. gender-specific records. We suppose these "across gender distributions" to be fair, as they suitably respect that women generally are slower than men. Introducing a statistical fairness measure, we provide a tool to assess the fairness of prize rank distributions. Finally, we evaluate commonly used prize rank distributions regarding their gender equity. For our investigations, we focus on triathlon. In triathlon competitions, often women have the same number of prize ranks as men, which might be considered fair. However, it will turn out that, from the perspective of performance, in many competitions it would have been much fairer to assign more prize ranks to men than to women. We shortly show that this result also applies to other endurance sports and discuss possible practical implications.